51.2k views
1 vote
Please me answer this question

Please me answer this question-example-1

2 Answers

3 votes

Answer:

x=11, y=13

Step-by-step explanation:

3x-2y=7

3x-2(x+2)=7 . - x + = - -2*+2=-4

3x-2x-4=7

1x-4=7

x=7+4

x=11

y=x+2

y=11+2

y=13

User BenLaz
by
4.9k points
4 votes
Answer:
(11, 13)
Step-by-step explanation:
The first step when you multiply -2 times 2 would equal -4
Then you would
3x-2x-4=7
x-4=7
x=11
y=x+2
y=11+2
y=13
The error Carolyn made was not multiplying the negative and positive number right.
User David Jacquel
by
5.5k points